PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI KELAS V UPT SD NEGERI 173299 PANIARAN - Sianturi, Nadya Fransiska; Juliana; Eka Kartika Silalahi; Darinda Sofia Tanjung; Dyan Wulan Sari HS; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to determine the influence of the Student Team Achievement Division type cooperative learning model on the learning outcomes of grade V students in the science subject at UPT SD Negeri 173299 Paniaran for the 2024/2025 Academic Year. This study uses a quantitative research method. The population in this study is all students of grade V of the State Elementary School UPT State Elementary School 173299 Paniaran consisting of 34 students. Sampling using Total Sampling. Those involved in this study were students of class V of SD Negeri 173299 Paniaran consisting of 20 males and 14 females. To find out the initial ability of students, researchers conducted a pretest with an average score of 53.52. After the researcher used the Student Team Achievement Divison model, it showed that student learning outcomes increased with an average of 81.41 good categories. This study can be proven from the results of the calculation of the correlation coefficient of 0.765, meaning R_hitung (0.765) ≥ R_tabel (0.338). So Ha accepted. So there is a strong influence between the Student Team Achievement Division model on the learning outcomes of students in grade V of SD Negeri 173299 Paniaran. It can be seen from the results of the t-test test which is 6,721 ≥ 1,690 with a significant level (⍺=0.05). Thus Ha was accepted. This shows that there is a significant positive influence of the use of the Student Team Achievement Division learning model on the teaching outcomes of students in grade V of the State Elementary School 173299 Paniaran for the 2024/2025 Academic Year.